«Who would not want your school get up there?»: Voices that echo on the Brazilian external evaluations applied in the micro-region schools of Ubá / MG - Pereira Vicente, Isabela (Pontificia Universidad Católica del Perú, 2017)
The purpose of this article is to present the results of a survey that examined theimpact of external evaluations in teaching in public schools of micro-region of Ubá(MRUbá), Minas Gerais. The methodology included an investigation into threeschools, on-site observations, semi-structured interviews with teachers, literatureon the subject and qualitative data analysis. The «voices» that echoed the schoolssignaled to the logic of accountability, accountability, the pressure for results, the(dis) belief in IDEB, of aspects relating to competition, among others. The dataenabled us to realize that teachers are greatly affected by the current evaluationmodel, whose measurement mechanisms the blaming and also to school, besidesgenerating rankings that are increasingly reinforcing a competitive environment.